Van Dijk, Teun A. (coord.). Racismo y discurso en América Latina. Barcelona: Gedisa, 2007. 423 págs. ISBN: 978-84-9784-179-5 - Rodríguez Muñoz, Francisco J. (Discurso & Sociedad, 2007)
Van Dijk, Teun A. (coord.). Racismo y discurso en América Latina. Barcelona: Gedisa, 2007. 423 págs. ISBN: 978-84-9784-179-5.